A study on the low-latitude daytime E region plasma irregularities using coordinated VHF radar, rocket-borne, and ionosonde observations - Patra, A.K.; Rao, N. Venkateswara; Phanikumar, D.V.; Chandra, H.; Das, U.; Sinha, H.S.S.; Pant, T.K.; Sripathi, S. (My University, 2009)
In this paper we study the off-electrojet low-latitude daytime E region plasma irregularities using first multi-instrument observations in India made during July 2004 by the MST radar from Gadanki (13.5°N, 79.2°E, magnetic latitude 6.4°N), Langmuir probe on board the RH-300 Mk II rocket, and ionosonde from Sriharikota (13.6°N, 80.2°E, magnetic latitude 6.4°N). Radar echoes were confined to altitudes below 105 km and were observed in the form of a descending echoing layer with the descent rate of 1 km/h. Virtual height of the E layer, as observed by ionosonde, shows identical descending behavior. A detailed analysis based on the radar and ionosonde observations shows that the radar echoes are related to the range spread in the ionogram. Rocket observations made on 23 July 2004 revealed weak plasma irregularities with scale sizes more than 100 m and no noticeable irregularity at shorter scales. The spectral slope of the irregularities observed by the rocket probe is found to be −4 for scales in between 1 km and 100 m. During the rocket launch, radar did not detect any echo conforming that the small-scale irregularities were not present. Examination of concurrent observations of neutral wind made by TIMED Doppler interferometry suggests that zonal wind plays a crucial role in forming electron density layers, which become unstable via the gradient drift instability with background electric field or/and zonal neutral wind generating low-latitude E region plasma irregularities.
Keywords: VHF radar; MST radar; E region plasma irregularities; Rocket-borne; Ionosonde observations